Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Taking the pulse of the world's raptors — A systematic quantitative review of wildlife rehabilitation centre admissions - Connor T. Panter; Heather E. Bullock; Mark Brown; Devvratsinh Mori; Lindy J. Thompson (Biological Conservation, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The effects of hydroelasticity on stringer-stiffened composite panels in water impacts: An experimental study - Connor Pearson; Nicola Shepherd; Mark Battley; Tom Allen (Ocean Engineering, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Assessment of the anticonvulsant activity of Myrica gale L., a traditional Irish plant in ethnoveterinary medicine, using a 4-AP induced seizure, electrophysiological model, in vitro - Sophie Whyms; Gaia Scalabrino; Kate Connor; Shipra Nagar; Maria Pigott; Helen Sheridan; Mark Cunningham (Phytochemistry Letters, 2025)

Neonatal sevoflurane exposure induces plasma biomarkers of inflammation in infant rhesus macaques - Greena Kim; Kaitlyn Love; Fawn Connor-Stroud; Mark G. Baxter; Maria Alvarado; Jessica Raper (Neurotoxicology and Teratology, 2025)

The effect of pasture-fed vs total mixed ration (TMR)-fed cheese on circulating fatty acid concentrations in middle-aged, overweight adults - Martina Rooney; Aileen O'Connor; Simone Dunne; Mark Timlin; André Brodkorb; Jeremiah J. Sheehan; Tom F. O'Callaghan; Michael O'Donovan; Deirdre Hennessy; Karina Pierce; Eileen R. Gibney; Emma L. Feeney (International Dairy Journal, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Postglacial Recolonization of the Southern Ocean by Elephant Seals Occurred From Multiple Glacial Refugia - Andrew A. Berg; Megan Askew; Frederik V. Seersholm; Alexander J. F. Verry; A. Rus Hoelzel; Andreanna Welch; Karen Greig; Richard Walter; Michael Knapp; Axel Barlow; Johanna L. A. Paijmans; Jonathan M. Waters; et al. (Global Change Biology, 2025)
The Southern Ocean is warming more rapidly than other parts of our planet. How this region's endemic biodiversity will respond to such changes can be illuminated by studying past events through genetic analyses of time‐series data sets, including historic and fossil remains. Archaeological and subfossil remains show that the southern elephant seal ( Mirounga leonina ) was common along the coasts of Australia and New Zealand in the recent past. This species is now mostly confined to sub‐Antarctic islands and the southern tip of South America. We analyzed ancient seal samples from Australia (Tasmania), New Zealand and the Antarctic mainland to examine how southern elephant seals have responded to a changing climate and anthropogenic pressures during the Holocene. Our analyses show that these seals formed part of a broader Australasian lineage, comprising seals from all sampled locations from the south Pacific sector of the Southern Ocean. Our study demonstrates that southern elephant seal populations have dynamically altered both range and population sizes under climatic and human pressures over surprisingly short evolutionary timeframes for such a large, long‐lived mammal.

Antimicrobial resistant Enterobacterales of clinical importance in mute swans - Aneta Kovarova; Graham Prole; Maeve Louise Farrell; Mark Maguire; Louise Catherine Murphy; Alexandra Chueiri; Louise O'Connor; Georgios Miliotis; Dearbháile Morris; Liam P. Burke (Science of The Total Environment, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Dynamic rates of Freshwater Drum near the northern extent of their range: evidence of environment-recruitment relationships - Marshall Stuart; Nicholas Kludt; Mark A. Pegg; Federica Montesanto; Cade Lyon; Connor J. Chance-Ossowski (Environmental Biology of Fishes, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

On the influence of flow-front orientation on stringer stiffened composite panels in water impacts - Connor Pearson; Marius de Mourgues; Mark Battley; Veronique Michaud; John Little; Guillaume Verdier; Tom Allen (Ocean Engineering, 2024)

Reimagining the language of engagement in a post-stakeholder world - Mark S. Reed; Bethann Garramon Merkle; Elizabeth J. Cook; Caitlin Hafferty; Adam P. Hejnowicz; Richard Holliman; Ian D. Marder; Ursula Pool; Christopher M. Raymond; Kenneth E. Wallen; David Whyte; Marta Ballesteros; et al. (Sustainability Science, 2024)
Language matters in shaping perceptions and guiding behaviour. The term stakeholder is widely used, yet little attention is paid to the possibility that its use may inadvertently perpetuate colonial narratives and reinforce systemic inequities. In this article, we critically examine the limitations of the stakeholder concept and its ambiguity, normativity, and exclusionary implications. We emphasise the importance of using language that gives a voice to marginalised groups, promotes inclusion and equity, and fosters meaningful and reflexive participation in decision-making processes. In critiquing the use of the term and calling for alternative practices, we aim to contribute to the decolonisation of research norms and the creation of more inclusive and equitable societies. Therefore, rather than advocating a single alternative term, we suggest a focus on the people, places, and species affected by decisions, interventions, projects, and issues.

GPS-derived environmental exposures during pregnancy and early postpartum – Evidence from the madres cohort - Li Yi; Yan Xu; Sydney O'Connor; Jane Cabison; Marisela Rosales; Daniel Chu; Thomas A. Chavez; Mark Johnson; Tyler B. Mason; Sandrah P. Eckel; Theresa M. Bastain; Carrie V. Breton; et al. (Science of The Total Environment, 2024)

An interdisciplinary synthesis of floodplain ecosystem dynamics in a rapidly deglaciating watershed - Christopher J. Sergeant; Jonathan W. Moore; Diane C. Whited; Kara J. Pitman; Mark Connor; Erin K. Sexton (Science of The Total Environment, 2024)

Increasing Lung Cancer Screening for High-Risk Smokers in a Frontier Population - Mark Dignan; Kristin Cina; Michele Sargent; Margaret O’Connor; Romaine Tobacco; Linda Burhansstipanov; Sheikh Ahamed; David White; Daniel Petereit (Journal of Cancer Education, 2024)

Utilisation of molecularly imprinting technology for the detection of glucocorticoids for a point of care surface plasmon resonance (SPR) device - Chester Blackburn; Mark V. Sullivan; Molly I. Wild; Abbie J. O’ Connor; Nicholas W. Turner (Analytica Chimica Acta, 2024)

Reducing Barriers to Living Shorelines Through Sea Grant Extension Programs - Sara Martin; Savanna Barry; Armando Ubeda; Vincent Encomio; Mark Clark; Rick O’Connor; Mandy Baily; Eric Sparks (Oceanography, 2024)
Natural shorelines provide ecosystem services that are integral to maintaining healthy and resilient coastal ecosystems and communities. However, anthropogenic and environmental stressors are reducing the extent of natural shorelines, and thus, their capacity to provide critical ecosystem services. Unfortunately, the most common shoreline management strategies involve hardened structures (e.g., bulkheads and seawalls) that are known to impair coastal ecosystems. Living shorelines offer a more environmentally friendly alternative to this shoreline hardening. To increase the adoption of living shorelines, the Mississippi-Alabama Sea Grant Consortium and Florida Sea Grant have produced guidance documents, offered technical assistance, constructed demonstration sites, and hosted trainings for property owners, contractors, and other practitioners. This article summarizes those efforts, details the results that have been achieved, and outlines existing barriers to further living shoreline implementation in the region.

Measurement theory and paleobiology - Kjetil Lysne Voje; James G. Saulsbury; Jostein Starrfelt; Daniel Varajão Latorre; Alexis Rojas; Vilde Bruhn Kinneberg; Lee Hsiang Liow; Connor J. Wilson; Erin E. Saupe; Mark Grabowski (Trends in Ecology & Evolution, 2023)

Longitudinal carriage of antimicrobial resistant Enterobacterales in healthy individuals in Ireland - Assessing the impact of recreational water use on duration of carriage - Maeve Louise Farrell; Alexandra Chueiri; Mark Maguire; Aneta Kovářová; Georgios Miliotis; Louise O'Connor; Francesca McDonagh; Sinead Duane; Martin Cormican; Genevieve Devane; Alma Tuohy; Niall DeLappe; et al. (Science of The Total Environment, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Active debris removal: A review and case study on LEOPARD Phase 0-A mission - Mithun Poozhiyil; Manu H. Nair; Mini C. Rai; Alexander Hall; Connor Meringolo; Mark Shilton; Steven Kay; Danilo Forte; Martin Sweeting; Nikki Antoniou; Victoria Irwin (Advances in Space Research, 2023)

Wild salmon enumeration and monitoring using deep learning empowered detection and tracking - William I. Atlas; Sami Ma; Yi Ching Chou; Katrina Connors; Daniel Scurfield; Brandon Nam; Xiaoqiang Ma; Mark Cleveland; Janvier Doire; Jonathan W. Moore; Ryan Shea; Jiangchuan Liu (Frontiers in Marine Science, 2023)
Pacific salmon have experienced declining abundance and unpredictable returns, yet remain vital to livelihoods, food security, and cultures of coastal communities around the Pacific Rim, creating a need for reliable and timely monitoring to inform sustainable fishery management. Currently, spawning salmon abundance is often monitored with in-river video or sonar cameras. However, reviewing video for estimates of salmon abundance from these programs requires thousands of hours of staff time, and data are typically not available until after the fishing season is completed. Computer vision deep learning can enable rapid and reliable processing of data, with potentially transformative applications in salmon population assessment and fishery management. Working with two First Nations fishery programs in British Columbia, Canada, we developed, trained, and tested deep learning models to perform object detection and multi-object tracking for automated video enumeration of salmon passing two First Nation-run weirs. We gathered and annotated more than 500,000 frames of video data encompassing 12 species, including seven species of anadromous salmonids, and trained models for multi-object tracking and species detection. Our top performing model achieved a mean average precision (mAP) of 67.6%, and species-specific mAP scores > 90% for coho and > 80% for sockeye salmon when trained with a combined dataset of Kitwanga and Bear Rivers’ salmon annotations. We also tested and deployed a prototype for a real-time monitoring system that can perform computer vision deep learning analyses on site. Computer vision models and off-grid monitoring systems show promise for automated counting and species identification. A key future priority will be working with stewardship practitioners and fishery managers to apply salmon computer vision, testing and applying edge-capable computing solutions for in-situ analysis at remote sites, and developing tools for independent user-led computer vision analysis by non-computer scientists. These efforts can advance in-season monitoring and decision making to support adaptive management of sustainable wild salmon fisheries.

Assessing the impact of recreational water use on carriage of antimicrobial resistant organisms - Maeve Louise Farrell; Alexandra Chueiri; Louise O'Connor; Sinead Duane; Mark Maguire; Georgios Miliotis; Martin Cormican; Brigid Hooban; Anne Leonard; William H. Gaze; Genevieve Devane; Alma Tuohy; et al. (Science of The Total Environment, 2023)

A Hansel & Gretel breadcrumb-style dynamically deployed communication network paradigm using mesh topology for planetary subsurface exploration - Wolfgang Fink; Connor Fuhrman; Andres Nuncio Zuniga; Mark Tarbell (Advances in Space Research, 2023)

Exploratory analysis of machine learning techniques in the Nevada geothermal play fairway analysis - Connor M. Smith; James E. Faulds; Stephen Brown; Mark Coolbaugh; Jacob DeAngelo; Jonathan M. Glen; Erick R. Burns; Drew L. Siler; Sven Treitel; Eli Mlawsky; Michael Fehler; Chen Gu; et al. (Geothermics, 2023)

The strong activity of noctilucent clouds at middle latitudes in 2020 - Peter Dalin; Hidehiko Suzuki; Nikolay Pertsev; Vladimir Perminov; Nikita Shevchuk; Egor Tsimerinov; Mark Zalcik; Jay Brausch; Tom McEwan; Iain McEachran; Martin Connors; Ian Schofield; et al. (Polar Science, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Effect of rapid weight loss incorporating hot salt water immersion on changes in body mass, blood markers, and indices of performance in male mixed martial arts athletes - John Connor; Mark Germaine; Conor Gibson; Philip Clarke; Brendan Egan (European Journal of Applied Physiology, 2022)
Purpose To investigate the effects of rapid weight loss (RWL), incorporating comparison of hot water immersion (HWI) in fresh or salt water, on changes in body mass, blood markers, and indices of performance in mixed martial arts athletes. Methods In a crossover design comparing fresh water (FWB) to salt water (SWB; 5.0%wt/vol Epsom salt) bathing, 13 males performed 20 min of HWI (~ 40.3 °C) followed by 40 min wrapped in a heated blanket, twice in sequence (2 h total). Before bathing, ~ 26 to ~ 28 h of fluid and dietary restriction was undertaken, and ~ 24 to ~ 26 h of a high carbohydrate diet and rehydration was undertaken as recovery. Results During the entire RWL process, participants lost ~ 5.3% body mass. Body mass lost during the 2 h hot bath protocol was 2.17 ± 0.81 kg (~ 2.7% body mass) and 2.24 ± 0.64 kg (~ 2.8% body mass) for FWB and SWB, respectively ( P = 0.647 between trials). Blood urea nitrogen, creatinine, sodium, chloride, hemoglobin, and hematocrit were increased (all P < 0.05), and plasma volume was decreased (~ 14%; P < 0.01), but did not differ between FWB and SWB, and were similar to baseline values after recovery. No indices of performance (e.g., countermovement jump, isometric strength, and functional threshold power) were impacted when RWL was followed by the recovery process. Conclusion Under the conditions of this hot bath protocol, fluid loss was not augmented by the addition of ~ 5.0%wt/vol of Epsom salt during HWI, and RWL of ~ 5.3% body mass followed by > 24 h of recovery did not impact indices of performance.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Opening Doors to Training Medical Toxicology Fellows from All Residency Backgrounds - Louise Kao; Michele Burns; Christine Murphy; Evan Schwarz; Steve Aks; Kavita Babu; Gillian Beauchamp; Rana Biary; Michele Burns; Nathan Charlton; Cathleen Clancy; Jonathan Ford; et al. (Journal of Medical Toxicology, 2022)

Anticipating and Adapting to the Future Impacts of Climate Change on the Health, Security and Welfare of Low Elevation Coastal Zone (LECZ) Communities in Southeastern USA - Thomas Allen; Joshua Behr; Anamaria Bukvic; Ryan S. D. Calder; Kiki Caruson; Charles Connor; Christopher D’Elia; David Dismukes; Robin Ersing; Rima Franklin; Jesse Goldstein; Jonathon Goodall; et al. (Journal of Marine Science and Engineering, 2021)
Low elevation coastal zones (LECZ) are extensive throughout the southeastern United States. LECZ communities are threatened by inundation from sea level rise, storm surge, wetland degradation, land subsidence, and hydrological flooding. Communication among scientists, stakeholders, policy makers and minority and poor residents must improve. We must predict processes spanning the ecological, physical, social, and health sciences. Communities need to address linkages of (1) human and socioeconomic vulnerabilities; (2) public health and safety; (3) economic concerns; (4) land loss; (5) wetland threats; and (6) coastal inundation. Essential capabilities must include a network to assemble and distribute data and model code to assess risk and its causes, support adaptive management, and improve the resiliency of communities. Better communication of information and understanding among residents and officials is essential. Here we review recent background literature on these matters and offer recommendations for integrating natural and social sciences. We advocate for a cyber-network of scientists, modelers, engineers, educators, and stakeholders from academia, federal state and local agencies, non-governmental organizations, residents, and the private sector. Our vision is to enhance future resilience of LECZ communities by offering approaches to mitigate hazards to human health, safety and welfare and reduce impacts to coastal residents and industries.

Characterizing the movements and habitat use of two fish species of concern in a regulated ecosystem - Lysel Garavelli; Shannon E. Blackburn; Allan T. Scholz; Jason M. Connor; Mark C. Paluch; Jason A. Olson; Brian J. Bellgraph (Hydrobiologia, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Mechanism and role of seeded native grasses to immobilize nitrogen on harvested blanket peat forests for protection of water courses - Zaki-ul-Zaman Asam; Connie O’Driscoll; Mohsin Abbas; Mark O’Connor; Muhammad Waqas; Mohammad Rehan; Abdul-Sattar Nizami; Liwen Xiao (Environmental Science and Pollution Research, 2021)

Non-Newtonian Effects on Patient-Specific Modeling of Fontan Hemodynamics - Zhenglun Wei; Shelly Singh-Gryzbon; Phillip M. Trusty; Connor Huddleston; Yingnan Zhang; Mark A. Fogel; Alessandro Veneziani; Ajit P. Yoganathan (Annals of Biomedical Engineering, 2020)

Analysis of Inlet Velocity Profiles in Numerical Assessment of Fontan Hemodynamics - Zhenglun Alan Wei; Connor Huddleston; Phillip M. Trusty; Shelly Singh-Gryzbon; Mark A. Fogel; Alessandro Veneziani; Ajit P. Yoganathan (Annals of Biomedical Engineering, 2019)

Sustainable Harvesting of the Ecosystem Engineer Corallina officinalis for Biomaterials - Caroline L. Magill; Christine A. Maggs; Mark P. Johnson; Nessa O’Connor (Frontiers in Marine Science, 2019)

Combined effects of warming and nutrients on marine communities are moderated by predators and vary across functional groups - Lydia White; Ian Donohue; Mark C. Emmerson; Nessa E. O’Connor (Global Change Biology, 2018)
Warming, nutrient enrichment and biodiversity modification are among the most pervasive components of human‐induced global environmental change. We know little about their cumulative effects on ecosystems; however, even though this knowledge is fundamental to predicting and managing their consequences in a changing world. Here, we show that shifts in predator species composition can moderate both the individual and combined effects of warming and nutrient enrichment in marine systems. However, all three aspects of global change also acted independently to alter different functional groups in our flow‐through marine rock‐pool mesocosms. Specifically, warming reduced macroalgal biomass and assemblage productivity, whereas enrichment led to increased abundance of meso‐invertebrate consumers, and loss of predator species led to increased gastropod grazer biomass. This disparity in responses, both across trophic levels (macroalgae and intermediate consumers), and between detecting additive effects on aggregate measures of ecosystem functioning, yet interactive effects on community composition, illustrates that our forecasting ability depends strongly on the level of ecological complexity incorporated within global change experiments. We conclude that biodiversity change—and loss of predator species in particular—plays a critical and overarching role in determining how ecological communities respond to stressors.

Dietary lipophilic iron accelerates regional brain iron-load in C57BL6 mice - Douglas G. Peters; Carson J. Purnell; Michael P. Haaf; Qing X. Yang; James R. Connor; Mark D. Meadowcroft (Brain Structure and Function, 2018)

Current Trends in Ligand Binding Real-Time Measurement Technologies - Stephanie Fraser; Judy Y. Shih; Mark Ware; Edward O’Connor; Mark J. Cameron; Martin Schwickart; Xuemei Zhao; Karin Regnstrom (The AAPS Journal, 2017)

Avian thermoregulation in the heat: efficient evaporative cooling in two southern African nightjars - Ryan S. O’Connor; Blair O. Wolf; R. Mark Brigham; Andrew E. McKechnie (Journal of Comparative Physiology B, 2017)

Reduced white matter MRI transverse relaxation rate in cognitively normal H63D-HFE human carriers and H67D-HFE mice - Mark D. Meadowcroft; Jianli Wang; Carson J. Purnell; Douglas G. Peters; Paul J. Eslinger; Elizabeth B. Neely; David J. Gill; Megha Vasavada; Fatima Ali-Rahmani; Qing X. Yang; James R. Connor (Brain Imaging and Behavior, 2016)

Reliable Support Design for Excavations in Brittle Rock Using a Global Response Surface Method - J. Connor Langford; Mark S. Diederichs (Rock Mechanics and Rock Engineering, 2015)

Genetic variation of the transthyretin gene in wild-type transthyretin amyloidosis (ATTRwt) - Jacquelyn L. Sikora; Mark W. Logue; Gloria G. Chan; Brian H. Spencer; Tatiana B. Prokaeva; Clinton T. Baldwin; David C. Seldin; Lawreen H. Connors (Human Genetics, 2015)

Managing Bay and Estuarine Ecosystems for Multiple Services - Lisa A. Needles; Sarah E. Lester; Richard Ambrose; Anders Andren; Marc Beyeler; Michael S. Connor; James E. Eckman; Barry A. Costa-Pierce; Steven D. Gaines; Kevin D. Lafferty; Hunter S. Lenihan; Julia Parrish; et al. (Estuaries and Coasts, 2015)

Solar Energy Development and Aquatic Ecosystems in the Southwestern United States: Potential Impacts, Mitigation, and Research Needs - Mark Grippo; John W. Hayse; Ben L. O’Connor (Environmental Management, 2015)

Nutrient and heavy metals in decaying harvest residue needles on drained blanket peat forests - Zaki-ul-Zaman Asam; Mika Nieminen; Annu Kaila; Raija Laiho; Sakari Sarkkola; Mark O’Connor; Connie O’Driscoll; Afshan Sana; Michael Rodgers; Xinmin Zhan; Liwen Xiao (European Journal of Forest Research, 2014)

Quantifying the sensitivity of ephemeral streams to land disturbance activities in arid ecosystems at the watershed scale - Ben L. O’Connor; Yuki Hamada; Esther E. Bowen; Mark A. Grippo; Heidi M. Hartmann; Terri L. Patton; Robert A. Van Lonkhuyzen; Adrianne E. Carr (Environmental Monitoring and Assessment, 2014)

Next Generation Ligand Binding Assays—Review of Emerging Real-Time Measurement Technologies - Stephanie Fraser; Mark Cameron; Edward O’Connor; Martin Schwickart; Michael Tanen; Mark Ware (The AAPS Journal, 2014)

Spatial and seasonal variation of peatland-fed riverine macroinvertebrate and benthic diatom assemblages and implications for assessment: a case study from Ireland - Connie O’Driscoll; Elvira de Eyto; Michael Rodgers; Mark O’Connor; Zaki-ul-Zaman Asam; Martyn Kelly; Liwen Xiao (Hydrobiologia, 2014)

Genetic polymorphisms associated with exertional rhabdomyolysis - Patricia A. Deuster; Carmen L. Contreras-Sesvold; Francis G. O’Connor; William W. Campbell; Kimbra Kenney; John F. Capacchione; Mark E. Landau; Sheila M. Muldoon; Elisabeth J. Rushing; Yuval Heled (European Journal of Applied Physiology, 2013)

On the dimensionality of ecological stability - Ian Donohue; Owen L. Petchey; José M. Montoya; Andrew L. Jackson; Luke McNally; Mafalda Viana; Kevin Healy; Miguel Lurgi; Nessa E. O'Connor; Mark C. Emmerson (Ecology Letters, 2013)
Ecological stability is touted as a complex and multifaceted concept, including components such as variability, resistance, resilience, persistence and robustness. Even though a complete appreciation of the effects of perturbations on ecosystems requires the simultaneous measurement of these multiple components of stability, most ecological research has focused on one or a few of those components analysed in isolation. Here, we present a new view of ecological stability that recognises explicitly the non‐independence of components of stability. This provides an approach for simplifying the concept of stability. We illustrate the concept and approach using results from a field experiment, and show that the effective dimensionality of ecological stability is considerably lower than if the various components of stability were unrelated. However, strong perturbations can modify, and even decouple, relationships among individual components of stability. Thus, perturbations not only increase the dimensionality of stability but they can also alter the relationships among components of stability in different ways. Studies that focus on single forms of stability in isolation therefore risk underestimating significantly the potential of perturbations to destabilise ecosystems. In contrast, application of the multidimensional stability framework that we propose gives a far richer understanding of how communities respond to perturbations.

Genome-wide study identifies two loci associated with lung function decline in mild to moderate COPD - Nadia N. Hansel; Ingo Ruczinski; Nicholas Rafaels; Don D. Sin; Denise Daley; Alla Malinina; Lili Huang; Andrew Sandford; Tanda Murray; Yoonhee Kim; Candelaria Vergara; Susan R. Heckbert; et al. (Human Genetics, 2013)

Optimization of LY545694 Tosylate Controlled Release Tablets Through Pharmacoscintigraphy - Evelyn D. Lobo; Mark D. Argentine; David C. Sperry; Alyson Connor; John McDermott; Lloyd Stevens; Ahmad Almaya (Pharmaceutical Research, 2012)

A Potential Solution to Mitigate Phosphorus Release Following Clearfelling in Peatland Forest Catchments - Connie O’Driscoll; Michael Rodgers; Mark O’Connor; Zaki-ul-Zaman Asam; Elvira de Eyto; Russell Poole; Liwen Xiao (Water, Air, & Soil Pollution, 2011)

Near infrared spectroscopy-derived interstitial hydrogen ion concentration and tissue oxygen saturation during ambulation - Stuart M. C. Lee; Mark S. F. Clarke; Daniel P. O’Connor; Leah Stroud; Gwenn E. C. Ellerby; Babs R. Soller (European Journal of Applied Physiology, 2011)

Stability of algorithms for a two domain natural convection problem and observed model uncertainty - Jeffrey Mark Connors; Benjamin Ganis (Computational Geosciences, 2011)

Neuropeptidomic Components Generated by Proteomic Functions in Secretory Vesicles for Cell–Cell Communication - Vivian Hook; Steven Bark; Nitin Gupta; Mark Lortie; Weiya D. Lu; Nuno Bandeira; Lydiane Funkelstein; Jill Wegrzyn; Daniel T. O’Connor; Pavel Pevzner (The AAPS Journal, 2010)

Quetiapine augmentation of paroxetine CR for the treatment of refractory generalized anxiety disorder: preliminary findings - Naomi M. Simon; Kathryn M. Connor; Richard T. LeBeau; Elizabeth A. Hoge; John J. Worthington; Wei Zhang; Jonathan R. T. Davidson; Mark H. Pollack (Psychopharmacology, 2008)

Sodium Zeolite A Supplementation and Its Impact on the Skeleton of Dairy Calves - K. K. Turner; B. D. Nielsen; C. I. O’Connor-Robison; D. S. Rosenstein; B. P. Marks; F. H. Nielsen; M. W. Orth (Biological Trace Element Research, 2008)

Spatial Relationships Between Water Quality and Pesticide Application Rates in Agricultural Watersheds - John W. Hunt; Brian S. Anderson; Bryn M. Phillips; Ron S. Tjeerdema; Nancy Richard; Val Connor; Karen Worcester; Mark Angelo; Amanda Bern; Brian Fulfrost; Dustin Mulvaney (Environmental Monitoring and Assessment, 2006)

Predicting Aggregation Kinetics of DU 145 Prostate Cancer Cells in Liquid-Overlay Culture - Kim C. O’Connor; Mark Z. Venczel (Biotechnology Letters, 2005)

Tryptophan?NAD+ pathway metabolites as putative biomarkers and predictors of peroxisome proliferation - Jane Delaney; Mark P. Hodson; Hansa Thakkar; Susan C. Connor; Brian C. Sweatman; Steve P. Kenny; Paul J. McGill; Julie C. Holder; Kathryn A. Hutton; John N. Haselden; Catherine J. Waterfield (Archives of Toxicology, 2005)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)